Persistent trigeminal artery aneurysms: case report and systematic review. (26th June 2019) - Diana, Francesco; Mangiafico, Salvatore; Valente, Vinicio; Wlderk, Andrea; Grillea, Giovanni; Colonnese, Claudio; Bartolo, Marcello
Abstract : Background: The persistent trigeminal artery (PTA) is an adult carotid-basilar anastomosis with debated pathologic aspects, such as its association with brain aneurysms. True trigeminal artery aneurysms are rare vascular anomalies, reported in a few case reports. Objective: To report our experience with a ruptured trigeminal artery aneurysm and to provide a systematic review of the literature in order to analyse potential links between the anatomic configuration of the PTA and PTA aneurysm (PTAA) type, and implications of each PTAA type for the diagnostic and therapeutic approach. Methods: We reviewed the medical literature on trigeminal artery aneurysms according to the PRISMA guidelines. Population characteristics, aneurysms features, and PTA type and side were assessed. Results: 40 previously published cases of PTAAs were included in the analysis. The mean age of subjects was 55 years, with a strong female predominance (77%). Four PTAAs were accidentally discovered, while 16 caused compressive symptoms and 20 were ruptured. Successful endovascular treatment was performed in 62% of cases. Conclusions: PTAAs are rare vascular anomalies, underdiagnosed in the presence of a trigemino-cavernous fistula. Parent vessel occlusion seems to be the best therapeutic option for ruptured or symptomatic unruptured PTAAs in Saltzman type II and III PTAs. Patency of the parent vessel is the main target in Saltzman type I PTA.